Cotton fabric crease-resistant finishing method for constructing semi-interpenetrating polymer network based on in-situ polymerization
By constructing a semi-interpenetrating polymerization network in cotton fabrics and using maleic anhydride, acrylic acid and isopentenol polyoxyethylene ether for in-situ polymerization, the problems of the existing anti-wrinkle finishing agent formaldehyde release and polycarboxylic acid finishing agent are solved, and the high cost and easy yellowing of the existing anti-wrinkle finishing agent is achieved, achieving an efficient and environmentally friendly anti-wrinkle finishing effect.
Patent Information
- Application Number
- CN202411889074.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-18
AI Technical Summary
The existing cotton fabric anti-wrinkle finishing agents have the risk of formaldehyde release and are harmful to the human body. The polycarboxylic acid finishing agents are costly, prone to yellowing, and unstable anti-wrinkle effect.
A method of constructing a semi-interpenetrating polymerization network based on in-situ polymerization is adopted. A polymerization network with anti-wrinkle effect is constructed by immersing cotton fabrics in the finishing solution, adding maleic anhydride, acrylic acid and isopentenol polyoxyethylene ether for reaction, and a polymerization network with anti-wrinkle effect is constructed through heating, dropwise addition of initiators, rolling and baking.
It has achieved a significant improvement in the wrinkle resistance effect of cotton fabrics, significantly improved wrinkle recovery angle, good whiteness, simple operation, easy access to raw materials, cost savings, and is conducive to environmental protection and industrial production.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of anti-wrinkle finishing of cotton fabrics, and in particular relates to an anti-wrinkle finishing method for cotton fabrics based on in-situ polymerization to construct a simulated semi-interpenetrating polymer network. Background Art
[0002] Cotton fabrics are widely used in daily clothing and home textile products due to their comfort, breathability and softness. However, cotton fabrics are prone to wrinkling, especially after wearing and washing, which affects the appearance and comfort. Therefore, the research on anti-wrinkle finishing technology becomes particularly important.
[0003] There are two main anti-wrinkle finishing methods: physical finishing and chemical finishing. Commonly used anti-wrinkle finishing agents in chemical finishing include melamine formaldehyde resin (MF), urea formaldehyde resin (UF) and etherified 2D resin (M2D). These finishing agents have good anti-wrinkle effects, but there is a risk of releasing formaldehyde, which is harmful to the human body. Therefore, it is urgent to develop formaldehyde-free anti-wrinkle finishing agents.
[0004] In recent years, researchers have been committed to developing green and harmless anti-wrinkle finishing agents. Polycarboxylic acid finishing agents, such as butane tetracarboxylic acid (BTCA), citric acid (CA) and maleic anhydride (MA), have attracted much attention due to their low toxicity and good environmental protection. However, these finishing agents also have problems: butane tetracarboxylic acid is expensive, citric acid is prone to yellowing when used, and the anti-wrinkle effect is unstable.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a method for anti-wrinkle finishing of cotton fabrics based on in-situ polymerization to construct a simulated semi-interpenetrating polymer network, thereby solving the problems raised in the above-mentioned background technology.
[0007] In order to solve the above technical problems, the basic concept of the technical solution adopted by the present invention is:
[0008] A method for anti-wrinkle finishing of cotton fabrics based on in-situ polymerization to construct a semi-interpenetrating polymer network comprises the following steps:
[0009] S1: Immerse the cotton fabric in the finishing solution at a bath ratio of 1:50;
[0010] S2: heating the finishing liquid containing cotton fabric, adding penetrant and sodium hypophosphite when the finishing liquid is heated to 35°C, and simultaneously dropping initiator to react;
[0011] S3: After the reaction is completed, the cotton fabric is pressed by a padder;
[0012] S4: pre-baking the cotton fabric at 80°C for 5 minutes and then baking at 160°C for 3 minutes to obtain wrinkle-resistant cotton fabric.
[0013] Optionally, the finishing liquid in step S1 includes monomers of maleic anhydride, acrylic acid and isopentanol polyoxyethylene ether in a molar ratio of 1:1:0.001-0.015, and the mass concentration of maleic anhydride is 80-100 g / L.
[0014] Optionally, in step S2, the penetrant is fatty alcohol polyoxyethylene ether, and the concentration of fatty alcohol polyoxyethylene ether is 1.5-2 g / L, and the concentration of sodium hypophosphite is 5-50 g / L.
[0015] Optionally, in step S2, the initiators are hydrogen peroxide and L-ascorbic acid, the mass of hydrogen peroxide accounts for 0.3% to 2% of the mass of the monomers used, and the mass of L-ascorbic acid accounts for 0.15% to 1% of the mass of the monomers used, and the two are added dropwise at the same time to form a redox initiation system. It should be noted that the mass of the monomers is the total mass of the three monomers of maleic anhydride, acrylic acid, and isopentanol polyoxyethylene ether.
[0016] Optionally, in step S2, the time for simultaneously adding hydrogen peroxide and L-ascorbic acid is 30-40 minutes. When adding hydrogen peroxide and L-ascorbic acid, a uniform dropping speed must be maintained, wherein the speed calculation formula for dropping hydrogen peroxide is dropping speed = total amount of hydrogen peroxide / titration time, and the speed calculation formula for dropping L-ascorbic acid is dropping speed = total amount of L-ascorbic acid / titration time.
[0017] Optionally, in step S2, when hydrogen peroxide and L-ascorbic acid are added dropwise, the reaction temperature is maintained between 35-65° C., and the reaction duration is 0.5-2.5 hours.
[0018] Optionally, in step S3, the liquid carrying rate of the cotton fabric can be controlled to be 80%-90% by pressing with a padder.
[0019] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art. Of course, any product implementing the present invention does not necessarily need to achieve all the advantages described below at the same time:
[0020] The present invention introduces the copolymerization of isopentanol polyoxyethylene ether macromonomer, and based on in-situ polymerization, together with maleic anhydride and acrylic acid, realizes the anti-wrinkle finishing effect of polycarboxylic acid, and at the same time, by means of the structural characteristics of isopentanol polyoxyethylene ether macromonomer, constructs a semi-interpenetrating polymerization network structure in cotton fabric, and realizes the anti-wrinkle finishing of cotton fabric. Under the optimal process conditions, the best anti-wrinkle finishing effect is obtained, the wrinkle recovery angle WRA is 252.2°, and the whiteness is 73.6. The wrinkle recovery angle WAR obtained from the original fabric sample is 141.5°, and the whiteness is 80.7. The wrinkle recovery angle is significantly improved, the anti-wrinkle effect is obvious, the whiteness retention effect is good, and the yellowing is small. The method of the present invention is simple to operate, the raw materials are easy to obtain, the enterprise cost can be saved, and it is beneficial to environmental protection and industrial production.
[0021] The specific embodiments of the present invention are described in further detail below. DETAILED DESCRIPTION
[0022] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0023] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0024] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0025] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0026] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0027] In this embodiment, a method for anti-wrinkle finishing of cotton fabrics based on in-situ polymerization to construct a semi-interpenetrating polymer network is provided, comprising the following steps:
[0028] S1: Immerse the cotton fabric in the finishing solution at a bath ratio of 1:50;
[0029] S2: heating the finishing liquid containing cotton fabric, adding penetrant and sodium hypophosphite when the finishing liquid is heated to 35°C, and simultaneously dropping initiator to react;
[0030] S3: After the reaction is completed, the cotton fabric is pressed by a padder;
[0031] S4: pre-baking the cotton fabric at 80°C for 5 minutes and then baking at 160°C for 3 minutes to obtain wrinkle-resistant cotton fabric.
[0032] In this embodiment, the finishing liquid in step S1 includes monomers of maleic anhydride, acrylic acid and isopentanol polyoxyethylene ether, and the molar ratio thereof is 1:1:0.001-0.015, and the mass concentration of maleic anhydride is 80-100 g / L.
[0033] In this embodiment, the penetrant in step S2 is fatty alcohol polyoxyethylene ether, and the concentration of fatty alcohol polyoxyethylene ether is 1.5-2 g / L, and the concentration of sodium hypophosphite is 5-50 g / L.
[0034] In this embodiment, the initiators in step S2 are hydrogen peroxide and L-ascorbic acid, the mass of hydrogen peroxide accounts for 0.3% to 2% of the mass of the monomers used, and the mass of L-ascorbic acid accounts for 0.15% to 1% of the mass of the monomers used, and the two are added dropwise simultaneously to form a redox initiation system.
[0035] In this embodiment, in step S2, the time for simultaneously adding hydrogen peroxide and L-ascorbic acid is 30-40 minutes, and a uniform dropping speed is required when adding hydrogen peroxide and L-ascorbic acid.
[0036] In this embodiment, in step S2, when hydrogen peroxide and L-ascorbic acid are added dropwise, the reaction temperature is maintained between 35-65° C., and the reaction duration is 0.5-2.5 hours.
[0037] In this embodiment, the liquid carrying rate of the cotton fabric can be controlled to be 80%-90% by the pressing of the padder in step S3.
[0038] It should be noted that all raw materials in the examples of the present invention were obtained through commercial sources.
[0039] Example 1: A cotton fabric (weight per square meter 477g, 10cm×10cm fabric sample with 230 warp yarns, 250 weft yarns, warp linear density 10.8tex, weft linear density 12.7tex, original fabric sample wrinkle recovery angle WAR of 141.5°, whiteness = 80.7) was immersed in a finishing solution at a bath ratio of 1:50, wherein the molar ratio of monomers maleic anhydride, acrylic acid, and isopentanol polyoxyethylene ether in the finishing solution was 1:1:0.008, and the mass concentration of maleic anhydride was 90g / L. After the finishing solution was heated When the temperature rises to 35°C, add 2g / L fatty alcohol polyoxyethylene ether and 40g / L sodium hypophosphite to the finishing liquid, and at the same time, add 0.7% hydrogen peroxide and 0.35% L-ascorbic acid. The titration time is between 30min and 40min, and the reaction temperature is maintained at 50°C. The reaction time is 1h. After the reaction is completed, the cotton fabric is rolled with a padder to control the liquid rate to 80%-90%. The cotton fabric is pre-baked at 80°C for 5min and baked at 160°C for 3min to obtain a wrinkle-resistant cotton fabric with a wrinkle recovery angle WRA of 252.2° and a whiteness of 73.6.
[0040] Example 2: A cotton fabric (weight per square meter 477g, 10cm×10cm fabric sample with 230 warp yarns, 250 weft yarns, warp linear density 10.8tex, weft linear density 12.7tex, original fabric sample wrinkle recovery angle WAR of 141.5°, whiteness = 80.7) was immersed in a finishing solution at a bath ratio of 1:50, wherein the molar ratio of monomers maleic anhydride, acrylic acid, and isopentanol polyoxyethylene ether in the finishing solution was 1:1:0.01, and the mass concentration of maleic anhydride was 80g / L. After the finishing solution was heated to When the temperature reaches 35°C, 1.5 g / L fatty alcohol polyoxyethylene ether and 35 g / L sodium hypophosphite are added to the finishing liquid, and 1% hydrogen peroxide and 0.5% L-ascorbic acid are added dropwise at the same time. The titration time is between 30 min and 40 min, and the reaction temperature is maintained at 55°C. The reaction time is 1.5 h. After the reaction is completed, the cotton fabric is rolled with a padder to control the liquid rate to 80%-90%. The cotton fabric is pre-baked at 80°C for 5 min and baked at 160°C for 3 min to obtain a wrinkle-resistant cotton fabric with a wrinkle recovery angle WRA of 242.7° and a whiteness of 71.6.
[0041] Example 3: A cotton fabric (weight per square meter 477g, 10cm×10cm fabric sample with 230 warp yarns, 250 weft yarns, warp linear density 10.8tex, weft linear density 12.7tex, original fabric sample wrinkle recovery angle WAR of 141.5°, whiteness = 80.7) was immersed in a finishing solution at a bath ratio of 1:50, wherein the molar ratio of monomers maleic anhydride, acrylic acid, and isopentanol polyoxyethylene ether in the finishing solution was 1:1:0.001, and the mass concentration of maleic anhydride was 70g / L. After the finishing solution was heated to a high temperature, the temperature of the finished solution was 100°C. When the temperature reaches 35°C, 0.5g / L fatty alcohol polyoxyethylene ether and 5g / L sodium hypophosphite are added to the finishing liquid, and 0.3% hydrogen peroxide and 0.15% L-ascorbic acid are added dropwise. The titration time is between 30min and 40min. The reaction temperature is maintained at 35°C and the reaction time is 0.5h. After the reaction is completed, the cotton fabric is rolled with a padder to control the liquid rate to 80%-90%. The cotton fabric is pre-baked at 80°C for 5min and baked at 160°C for 3min to obtain a wrinkle-resistant cotton fabric with a wrinkle recovery angle WRA of 220.0° and a whiteness of 70.7.
[0042] In all embodiments of the present invention, cotton fabrics with anti-wrinkle effect are formed by introducing isopentanol polyoxyethylene ether macromonomers and copolymerizing with maleic anhydride and acrylic acid. These embodiments all show significant anti-wrinkle effect, and the wrinkle recovery angle (WRA) is significantly improved.
[0043] Example 1: The wrinkle recovery angle reaches 252.2°, which is the most significant effect, indicating the best anti-wrinkle effect.
[0044] Example 2: The wrinkle recovery angle is 242.7°, which also shows good anti-wrinkle performance, but is slightly lower than that of Example 1.
[0045] Embodiment 3: The wrinkle recovery angle is 220.0°, which is slightly lower than that of the other two embodiments, but still maintains a good anti-wrinkle effect.
[0046] Secondly, in addition to the anti-wrinkle effect, all examples performed well in maintaining whiteness. The high whiteness index shows that the present technology does not have a significant negative impact on the appearance of cotton fabrics while resisting wrinkles.
[0047] The whiteness of Example 1 is 73.6, which is slightly lower than that of the other two examples, but still maintains a good whiteness.
[0048] The whiteness of Example 2 is 71.6, which is slightly reduced, but still has a small decrease compared with the original fabric sample.
[0049] The whiteness of Example 3 is 70.7, and the whiteness decreases most significantly, but the yellowing is small, which still meets industrial requirements.
[0050] The present invention is not limited to the above-mentioned embodiments. Anyone should be aware that any structural changes made under the enlightenment of the present invention, and any technical solutions that are the same or similar to the present invention, fall within the protection scope of the present invention. The technology, shape, and structural parts not described in detail in the present invention are all well-known technologies.
Claims
1. A method for anti-wrinkle finishing of cotton fabrics based on in-situ polymerization to construct a semi-interpenetrating polymer network, characterized in that: The following steps are involved: S1: Immerse the cotton fabric in the finishing solution at a bath ratio of 1:50; S2: heating the finishing liquid containing cotton fabric, adding penetrant and sodium hypophosphite when the finishing liquid is heated to 35°C, and simultaneously dropping initiator to react; S3: After the reaction is completed, the cotton fabric is pressed by a padder; S4: pre-baking the cotton fabric at 80°C for 5 minutes and then baking at 160°C for 3 minutes to obtain wrinkle-resistant cotton fabric.
2. The method for anti-wrinkle finishing of cotton fabrics based on in-situ polymerization to construct a semi-interpenetrating polymer network according to claim 1, characterized in that: The finishing liquid in step S1 includes monomers of maleic anhydride, acrylic acid and isopentanol polyoxyethylene ether in a molar ratio of 1:1:0.001-0.015, and the mass concentration of maleic anhydride is 80-100 g / L.
3. The method for anti-wrinkle finishing of cotton fabrics based on in-situ polymerization to construct a semi-interpenetrating polymer network according to claim 1, characterized in that: In step S2, the penetrant is fatty alcohol polyoxyethylene ether, and the concentration of fatty alcohol polyoxyethylene ether is 1.5-2 g / L, and the concentration of sodium hypophosphite is 5-50 g / L.
4. The method for anti-wrinkle finishing of cotton fabrics based on in-situ polymerization to construct a semi-interpenetrating polymer network according to claim 1, characterized in that: In step S2, the initiators are hydrogen peroxide and L-ascorbic acid, the mass of hydrogen peroxide accounts for 0.3% to 2% of the mass of the monomers used, and the mass of L-ascorbic acid accounts for 0.15% to 1% of the mass of the monomers used, and the two are added dropwise simultaneously to form a redox initiation system.
5. The method for anti-wrinkle finishing of cotton fabric based on in-situ polymerization to construct a semi-interpenetrating polymer network according to claim 1, characterized in that: In step S2, the hydrogen peroxide and L-ascorbic acid are added dropwise simultaneously for 30-40 minutes.
6. The method for anti-wrinkle finishing of cotton fabrics based on in-situ polymerization to construct a semi-interpenetrating polymer network according to claim 1, characterized in that: In step S2, when hydrogen peroxide and L-ascorbic acid are added dropwise, the reaction temperature is maintained between 35-65° C., and the reaction duration is 0.5-2.5 hours.
7. The method for anti-wrinkle finishing of cotton fabrics based on in-situ polymerization to construct a semi-interpenetrating polymer network according to claim 1, characterized in that: In step S3, the liquid carrying rate of the cotton fabric can be controlled to be 80%-90% by the pressing of the padder.